2016
DOI: 10.18632/aging.101064
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial proteomic profiling reveals increased carbonic anhydrase II in aging and neurodegeneration

Abstract: Carbonic anhydrase inhibitors are used to treat glaucoma and cancers. Carbonic anhydrases perform a crucial role in the conversion of carbon dioxide and water into bicarbonate and protons. However, there is little information about carbonic anhydrase isoforms during the process of ageing. Mitochondrial dysfunction is implicit in ageing brain and muscle. We have interrogated isolated mitochondrial fractions from young adult and middle aged mouse brain and skeletal muscle. We find an increase of tissue specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 47 publications
1
55
0
Order By: Relevance
“…Our data show that enriched mitochondrial fractions have characteristic lipidomic profiles specific to the age and type of tissue, echoing our findings in the mitochondrial proteome [43]. We find the brain mitochondrial lipidome is highly modulated with ageing, with fatty acids decreased in older animals.…”
Section: Discussionsupporting
confidence: 89%
“…Our data show that enriched mitochondrial fractions have characteristic lipidomic profiles specific to the age and type of tissue, echoing our findings in the mitochondrial proteome [43]. We find the brain mitochondrial lipidome is highly modulated with ageing, with fatty acids decreased in older animals.…”
Section: Discussionsupporting
confidence: 89%
“…Promising studies in transgenic mouse models of amyloidosis are currently ongoing in our laboratory. The physiological relevance of this approach is further highlighted by recent proteomic studies showing increased CAII in the mitochondria in aging and neurodegeneration (Pollard et al., 2016), as well as by our group's recent findings demonstrating the presence of multiple CA enzymes in amyloid plaques within the AD human brain (Drummond et al., 2017). …”
Section: Discussionmentioning
confidence: 58%
“…CA‐VA and CA‐VB have a mitochondrial localization (Ghandour, Parkkila, Parkkila, Waheed & Sly, 2000). CA‐II, known as cytoplasmic, was also recently shown by proteomic profiling to be increased in brain mitochondria in aging and neurodegeneration (Pollard, Shephard, Freed, Liddell & Chakrabarti, 2016). CA inhibitors (CAIs) are used to treat a variety of disorders including glaucoma, epilepsy, neuropsychiatric disorders, and acute mountain sickness (Aggarwal, Kondeti & McKenna, 2013; Fossati et al., 2016; Huang et al., 2010).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, the addition of recombinant CA9 enzyme promoted wound re-epithelialization [40]. Furthermore, a proteome study also revealed the involvement of CA2 protein in aging and neurodegeneration in a mouse [41]. Here, we demonstrated that LACCE promoted the regeneration of human keratinocyte cells by up-regulating CA2 expression.…”
Section: Discussionmentioning
confidence: 65%